Optimal bound for the number of (−1)-curves on extremal rational surfaces - Mustapha Lahyane (International Journal of Mathematics and Mathematical Sciences)
We give an optimal bound for the number of (−1)-curves on an extremal rational surface X under the assumption that −KX is numerically effective and having self-intersection zero. We also prove that a nonelliptic extremal rational surface has at most nine (−1)-curves.